ANALYSIS OF THE INFLUENCE OF EDUCATION LEVELS, TRANSFORMATIONAL LEADERSHIP, AND SELF-EFFICACY ON THE PERFORMANCE OF VILLAGE GOVERNMENT APPARATUS IN PURWOJATI DISTRICT, BANYUMAS REGENCY - Fatmah Bagis; Timbang Apit Afifah; Akhmad Darmawan; Naelati Tubastuvi; Mastur Mujib Ikhsani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to examine the role of education level, transformational leadership, and self-efficacy on the performance of village government officials in Purwojati District, Banyumas Regency. The sample came from the entire population, namely village government officials in Purwojati Regency totaling 180 respondents. This study uses a quantitative approach method. Social cognitive theory is used as the basis for the theory of the relationship between the variables studied. The data were processed using multiple linear regression analysis and the results showed that the level of education and self-efficacy had a positive and significant effect on performance, while transformational leadership had no effect on performance. Based on the test results of the adjusted R2 coefficient of determination of 55.90%. Keywords: Education Level, Transformational Leadership, Self-Efficacy, Performance